The dictionary of modern economics - Pearce, David W. (London : English Language Book Society/Macmillan, 1985)
There are over two thousand five hundred entries covering modern theory and practice, leading economists, international institutions, traditional concepts and recent controversies. Many business terms are also included. Each entry in the book contains cross references except in the few cases where a word or phrase is self contained, and the reader is encouraged to pursue these to build up a picture of a given area of economics.
ne 09/09/2021
Ref.
Keywords: Economics